Pengaruh Profitabilitas, Leverage, dan Komite Audit pada Environmental Disclosure dengan Kinerja Lingkungan sebagai Variabel Moderasi - Baihaqi, Khafidz; Wahyuningrum, Indah Fajarini Sri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2026)
This study examines the effect of profitability, leverage, and audit committee on environmental disclosure, with environmental performance as a moderating variable. It is motivated by the persistently low level of voluntary environmental disclosure among Indonesian manufacturing firms, despite existing regulatory frameworks. Using a quantitative causal-comparative design, this study analyzed 20 Basic Material sector companies listed on the Indonesia Stock Exchange during 2021–2024, yielding 80 units of analysis. Environmental disclosure was measured using seven indicators from the 2021 GRI standards, while environmental performance was assessed through the national PROPER rating system. Data were analyzed using multiple linear regression and moderated regression analysis. Results show that environmental performance has a significant positive effect on environmental disclosure, while profitability, leverage, and audit committee show no significant effects. Environmental performance significantly strengthens the effect of leverage on disclosure, but not the effects of profitability or audit committee. These findings support legitimacy and agency theory, highlighting environmental performance as a key driver and moderating mechanism of corporate environmental transparency.